Bismuth complexes with N/S coordination based metallopolymer as highly efficient photocatalyst for selective oxidation of styrene. (15th October 2021) - Wang, Qiuchen; Deng, Xiaoxu; Chen, Wenguang; Chen, Peng; Liu, Fei; Yin, Shuang-Feng
Graphical abstract: Highlights: First report of bismuth ion-containing N/S Coordination based metallopolymer photocatalyst. The Bi-N bond is beneficial for oxygen absorption and separation of charge carriers. It shows high photocatalytic activity and stability in selective oxidation of styrene using air. Abstract: Photocatalytic selective oxidation organic compounds to produce high additional value of products with air hold great promising in the chemical industry, but the photocatalyst often suffered from serious recombination of charge carriers, limited conversion efficiency, poor oxygen adsorption and stability. Here, a novel bismuth complexes with N/S coordination based metallopolymer (BiTMT) has been prepared by a facile wet-chemical method. It is confirmed that the weak interaction of Bi−N bonds not only acted as electron trapping site and charge bridge to facilitate the separation of photogenerated charge carrier, but also played an important role in the adsorption and activation of oxygen from air. BiTMT exhibits excellent conversion efficiency and stability in the selective oxidation of styrene using air as oxidant under visible light irradiation. This finding opens an avenue to design functional sites for photocatalytic selective oxidation and other applications.